(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
The study examines the contribution of an institutional qualification program to professional development in a state research support foundation. It describes the program’s structure, objectives, and operational tools, assessing its alignment with state regulations and federal governance guidelines. An exploratory and comparative approach was adopted, based on the analysis of official documents and academic studies. The results indicate that the initiative integrates training and career advancement, strengthens management practices, and contributes to administrative modernization and the improvement of services provided to society.